2020
DOI: 10.1128/jvi.01559-20
|View full text |Cite
|
Sign up to set email alerts
|

Development of Styrene Maleic Acid Lipid Particles as a Tool for Studies of Phage-Host Interactions

Abstract: The infection of a bacterium by a phage starts with attachment to a receptor molecule on the host cell surface by the phage. As receptor-phage interactions are crucial to successful infections, they are major determinants of phage host-range and by extension of the broader effects that phages have on bacterial communities. Many receptor molecules, particularly membrane proteins, are difficult to isolate because their stability is supported by their native membrane environments. Styrene maleic acid lipid partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As reviewed by Overduin and Esmaili, SMA is effective for solubilizing both monomeric and oligomeric proteins as well as those that are unstable, low-abundance, or lipid-dependent [ 13 ]. Extraction using polymers can be used to study specific interactions of membrane proteins with other membrane proteins [ 13 ], with lipids [ 122 , 135 , 136 , 137 , 138 ], and with ligands or substrates [ 115 , 116 , 126 , 128 , 139 ] and even to study phage–host interactions [ 140 ]. Following extraction with SMA, MPs can later be reconstituted back into lipid bilayers for functional studies [ 119 , 122 ].…”
Section: Applications Of Lipodiscs In Structural Biologymentioning
confidence: 99%
“…As reviewed by Overduin and Esmaili, SMA is effective for solubilizing both monomeric and oligomeric proteins as well as those that are unstable, low-abundance, or lipid-dependent [ 13 ]. Extraction using polymers can be used to study specific interactions of membrane proteins with other membrane proteins [ 13 ], with lipids [ 122 , 135 , 136 , 137 , 138 ], and with ligands or substrates [ 115 , 116 , 126 , 128 , 139 ] and even to study phage–host interactions [ 140 ]. Following extraction with SMA, MPs can later be reconstituted back into lipid bilayers for functional studies [ 119 , 122 ].…”
Section: Applications Of Lipodiscs In Structural Biologymentioning
confidence: 99%
“…Another important factor affecting formation of such nanodisc is a lipid type of which it was contained. Solubilization of the Gram-negative E. coli membranes upon PSMA addition yielded the nanodiscs with the size diameter of around 10 nm, while that of the Gram-positive B. subtilis membranes showed larger size between 50 and 100 nm [ 36 ]. Taken together with the DLS results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This approach enables a quantitative, real-time measurement of binding assays with relatively low concentrations of purified protein. The use of SMA-solubilised bacteria as a tool to isolate and study phage-receptor interactions has been investigated [ 69 ]. It was found that specific interactions could be detected between different phage and their target bacteria, which led to DNA ejection by the phage.…”
Section: Functional Insightsmentioning
confidence: 99%